2012
DOI: 10.1016/j.astropartphys.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Transition from galactic to extragalactic cosmic rays

Abstract: a b s t r a c tThe study of the transition between galactic and extragalactic cosmic rays can shed more light on the end of the galactic cosmic rays spectrum and the beginning of the extragalactic one. Three models of transition are discussed: ankle, dip and mixed composition models. All these models describe the transition as an intersection of a steep galactic component with a flat extragalactic one. Severe bounds on these models are provided by the Standard Model of galactic cosmic rays according to which t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 92 publications
(132 reference statements)
4
88
0
6
Order By: Relevance
“…Therefore, energies between 10 17 and 10 19 eV are expected to mark the transition from galactic to extragalactic sources (e. g. Aloisio et al 2012). The sources of ultra high energy cosmic rays (UHECRs) have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, energies between 10 17 and 10 19 eV are expected to mark the transition from galactic to extragalactic sources (e. g. Aloisio et al 2012). The sources of ultra high energy cosmic rays (UHECRs) have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The extragalactic origin of UHECRs, at least at energies above the ankle E > 10 19 eV, is widely accepted [18]. The propagation of UHECR through the intergalactic medium is conditioned primarily by astrophysical photon backgrounds and, if any, by the presence of [17].…”
Section: Transport Of Uhecrs Spectrum and Mass Compositionmentioning
confidence: 99%
“…A careful investigation of the transition region in the context of the dip and ankle models was carried out (see [18] and references therein), assuming an exponential cutoff in the galactic CR component. The authors concluded that the ankle model is basically ruled out by measurements of the depth of shower maximum, X max (E), and its RMS fluctuations.…”
Section: Transition Galactic-extragalactic Cosmic Raysmentioning
confidence: 99%
“…In fact, the conclusion about ruling out the ankle as transition feature has been already made in [61] and more recently in [62] from analysis of elongation curve X max (E). One can see from right-upper and right-lower panels of Fig.…”
Section: Pao Data: Energy Spectrum and Mass Compositionmentioning
confidence: 99%